2009
DOI: 10.1007/s11426-009-0240-7
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and in vitro antineoplastic drug-loaded trial of titania nanotubes prepared by anodic oxidation of a pure titanium

Abstract: TiO 2 nanotube (NT) arrays have been prepared by anodic oxidation of a Ti sheet, and carbon-deposited TiO 2 NT arrays have been prepared by annealing TiO 2 NT arrays in carbon atmosphere. The biocompatibility of the as-prepared NT arrays was investigated by observing the growth of osteosarcoma (MG-63) cells on the NT arrays. The application of the TiO 2 NT arrays as a drug delivery vehicle was investigated.Both the TiO 2 NTs and the carbon-modified TiO 2 NTs have good biocompatibility supporting the normal gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 21 publications
(30 reference statements)
1
14
0
Order By: Relevance
“…Metal oxide nanotubes, such as nanotubular titania (TiO 2 ), which were discovered in the 1990s, are non-toxic and potentially useful materials for many applications, including biomedical ones [128][129][130] and are thermally stable and corrosion resistant [131][132][133]. They have the same advantages associated with scale that are found in carbon nanotubes, and unlike carbon nanotubes, they can be manufactured at low cost by hydrothermal, electrochemical and surfactant template techniques, [132,134,135] This makes PPy/TiO2 nanocomposites a good candidates for drug delivery systems [131].…”
Section: Nanotubular Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal oxide nanotubes, such as nanotubular titania (TiO 2 ), which were discovered in the 1990s, are non-toxic and potentially useful materials for many applications, including biomedical ones [128][129][130] and are thermally stable and corrosion resistant [131][132][133]. They have the same advantages associated with scale that are found in carbon nanotubes, and unlike carbon nanotubes, they can be manufactured at low cost by hydrothermal, electrochemical and surfactant template techniques, [132,134,135] This makes PPy/TiO2 nanocomposites a good candidates for drug delivery systems [131].…”
Section: Nanotubular Structuresmentioning
confidence: 99%
“…They have the same advantages associated with scale that are found in carbon nanotubes, and unlike carbon nanotubes, they can be manufactured at low cost by hydrothermal, electrochemical and surfactant template techniques, [132,134,135] This makes PPy/TiO2 nanocomposites a good candidates for drug delivery systems [131]. However, TiO 2 have large bandgap and can be considered as semiconductor materials [136,137].…”
Section: Nanotubular Structuresmentioning
confidence: 99%
“…The biocompatibility of the as-prepared TNTs was studied by observing the growth of osteosarcoma (MG-63) cells on the TNT surface, and TNTs loaded with the antineoplastic drug were investigated by using MG-63 cells as targets and cisplatin as the model drug. 131 Their results demonstrated that TNTs show excellent biocompatibility and can be used as a drug delivery vehicle, with efficient drug loading and releasing ability to significantly suppress the growth of MG-63 cells. Moreover, Kalbacova et al demonstrated that TNTs can be used as a photocatalyst to kill cancer cells.…”
Section: Brain Tumorsmentioning
confidence: 99%
“…The geometry of TiO 2 nanotube as a membrane makes it appropriate for placement for both injected capsules and biomedical implant [2]. Xiao and his workers [3] showed outstanding biocompatibility of both TiO 2 nanotube arrays that prepared by anodisation and annealed in a carbon atmosphere. Application of drug delivery system was accomplished by various methods [4].…”
Section: Introduction:-mentioning
confidence: 99%